Ornamental Plant’s Potentials of Indonesian Native Rubiaceae Collected in Cibodas Botanical Garden - Dwinda Mariska Putri; Decky Indrawan Junaedi; R. Hendrian (Hasanuddin University, 2021)
Cibodas Botanical Garden (CBG) is an ex-situ plant conservation institution, maintaining living collection from various taxa including Rubiaceae. Most of Rubiaceae ornamental plants are introduced species with regard to their attractive characters. However, introduced species of ornamental plants is one of significant global plant invasion pathways. The aims of this research was to conduct inventory study of CBG’s Rubiaceae collection, to determine native and introduced species, and to bring out CBG’s native Rubiaceae potential as ornamental plants. The research was divided into two methods, field study and literature study. Field study was conducted by making inventory of Rubiaceae living collections and plant morphology observations. Literature study was conducted by obtaining data of plant distributions, utilization as ornamental plants, and also comparing domesticated species with CBG’s living collections. Results showed that CBG has collected 20 genera, 50 species and 116 specimens of Rubiaceae as living collections. There are 22 native species, 15 introduced species and 13 species that can not be determined. There are 5 species commonly utilized and cultivated as ornamental plants, 8 species are not known for their aesthetic characters but has potential as ornamental plants. These species are Gardenia pterocalyx Valeton, Hypobathrum frutescens Blume, H. racemosum (Roxb.) Kurz, Mycetia cauliflora Reinw., Pavetta montana Reinw. Ex Blume, Psychotria angulata Korth, P. montana Blume, and Wendlandia densiflora (Blume) DC. This study demonstrated that there is a promising potential from these lesser-known native Rubiaceae species for ornamental use. CBG should conduct more research about native species’s potential as ornamental plants.